Reversible Jahn–Teller Effect: Highlighting the Reversible Manganese Electroactivity in Na‐Rich Manganese Hexacyanoferrate Material for Li‐ and Na‐Ion Storage (Small Methods 1/2020). Issue 1 (9th January 2020) - Mullaliu, Angelo; Asenbauer, Jakob; Aquilanti, Giuliana; Passerini, Stefano; Giorgetti, Marco
Abstract : In article number 1900529 by Stefano Passerini, Marco Giorgetti, and co‐workers, synchrotron‐based extended X‐ray absorption fine structure (EXAFS) spectroscopy is applied on sodium‐rich manganese hexacyanoferrate materials upon electrochemical ion‐release and uptake. The modulation of the absorption coefficient, evaluated as the sum of the few photoelectron scattering contributions, is analyzed to disclose electroactivity of both manganese and iron species, as well as a reversible Jahn–Teller distortion affecting trivalent manganese.